Calcium-binding protein of chorioallantoic membrane: identification and development expression. - Tuan, R S (1977)
A calcium-binding protein (CaBP) which has a molecular weight of 100,000 and an isoelectric point of 8.0 has been isolated from the chorioallantoic membrane (CAM) of the chick embryo. Expression of the CaBP occurs simultaneously with the onset of calcium absorption from the egg shell by the CAM, and the temporal increase in CaBP activity is coincident with calcium deposition in the embryo. The CAM CaBP differs in properties from the CaBPs of the adult organs, including the vitamin-D-dependent protein of intestine.